Employing Ergonomic Standards in designing Educational Laboratory for Hand weaving - Dr. Hala Yousef Al-Osailan (المجلة الدولية للعلوم الإنسانية والاجتماعية)
Occupational safety is considered one of the fundamentals of the success of educational system, especially in light of the remarkable development in the Industrial Revolution and the change it brought in study patterns and educational strategies that aimed in building the educational outcomes compatible with the changing labor market .